1972
DOI: 10.1530/jrf.0.0290261
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Ultrastructural and Histochemical Studies of the Interstitial Cells of the Rat Testis During Fetal and Postnatal Development

Abstract: The interstitial cells of the albino rat testis were studied in animals ranging from the 15th day of fetal life until adulthood. The interstitial cells developed in two phases, a fetal phase from the 17th fetal day to the 2nd postnatal week and an adult phase from the 3rd week onwards. Lipid histochemical and ultrastructural techniques demonstrated the abundance of lipid droplets in the fetal interstitial cells and the paucity of lipid in the adult interstitial cells. The enzyme \g=D\5-3\g=b\-hydroxysteroiddeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
91
0
2

Year Published

1974
1974
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(105 citation statements)
references
References 18 publications
12
91
0
2
Order By: Relevance
“…FLCs are not uniformly distributed in the interstitial space of the GD21 testis but rather are found in discrete clusters (15); only 20 Ļ® 1% were present as single cell ( Table 2). The percentage of single cell decreased significantly from controls with DEHP exposures, and the average number of FLCs per cluster also was greater after DEHP (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…FLCs are not uniformly distributed in the interstitial space of the GD21 testis but rather are found in discrete clusters (15); only 20 Ļ® 1% were present as single cell ( Table 2). The percentage of single cell decreased significantly from controls with DEHP exposures, and the average number of FLCs per cluster also was greater after DEHP (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…28 The developmental differentiation of fetal gonads is greatly influenced by these fetal sources of steroids. 29 The differentiation of the fetal gonads is controlled by the homeobox or Hox genes. 30 In particular, the posterior most Hox-d and Hox-a genes are strongly expressed in the urino-genital system including the gonads; however, these genes are also required for the growth and differentiation of digits and toes.…”
Section: -23mentioning
confidence: 99%
“…The fetal population of Leydig cells differentiate during the fetal life and is still present at birth ( Figure 5) in all species studied to date (Lording and de Kretser, 1972;Mendis-Handagama et al, 1987;Kerr and Knell, 1988;Chemes, 1996;Ariyaratne and Mendis-Handagama, 2000;O'Shaughnessy et al, 2002O'Shaughnessy et al, , 2003 and continue to be present in the postnatal testis in rodents studied to date (Kerr and Knell, 1988;Ariyaratne and Mendis-Handagama, 2000;O'Shaughnessy et al, 2002O'Shaughnessy et al, , 2003. However, in humans, it is reported that fetal Leydig cells undergo cell atrophy postnatally (Chemes, 1996).…”
Section: Testis Interstitiummentioning
confidence: 99%